2019
DOI: 10.1002/cssc.201802809
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Abundance and Molecular Weight Characteristics of Technical Lignins by Attenuated Total Reflection‐FTIR Spectroscopy Combined with Multivariate Analysis

Abstract: Lignin is an attractive material for the production of renewable chemicals, materials and energy. However, utilization is hampered by its highly complex and variable chemical structure, which requires an extensive suite of analytical instruments to characterize. Here, we demonstrate that straightforward attenuated total reflection (ATR)‐FTIR analysis combined with principle component analysis (PCA) and partial least squares (PLS) modelling can provide remarkable insight into the structure of technical lignins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 46 publications
6
80
2
Order By: Relevance
“…Here, multivariate data analysis is a very helpful tool to "extract" details that are not available using conventional univariate analysis as shown also by other groups for lignins of different origin and pre-treatment method. 71,72 In a previous study, we also used chemometric processing of infrared data to specify differences of lignins obtained from six different Miscanthus genotypes including M. nagara (NagG10) and M. x giganteus (Gig35) separated by plant portions: stem versus leaf-derived lignins could be differentiated by their aromatic in-plane deformation signals at 1160 cm À1 corresponding to the monolignol substitution pattern. 61…”
Section: Structural Differences Of Isolated Ligninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, multivariate data analysis is a very helpful tool to "extract" details that are not available using conventional univariate analysis as shown also by other groups for lignins of different origin and pre-treatment method. 71,72 In a previous study, we also used chemometric processing of infrared data to specify differences of lignins obtained from six different Miscanthus genotypes including M. nagara (NagG10) and M. x giganteus (Gig35) separated by plant portions: stem versus leaf-derived lignins could be differentiated by their aromatic in-plane deformation signals at 1160 cm À1 corresponding to the monolignol substitution pattern. 61…”
Section: Structural Differences Of Isolated Ligninsmentioning
confidence: 99%
“…Here, multivariate data processing (such as partial component analysis, linear discriminant analysis, factorial discriminant analysis and partial least squares-discriminant analysis) proved to be a useful tool for origin specication of complex structures such as lignocellulosic biomass, especially lignin. 71,72,[93][94][95][96][97][98][99] Moreover, Brandt et al emphasized that quantication using HSQC is generally limited since pulse sequences are usually optimized for resolution and signal strength. In addition, signal relaxation might not be complete particularly for some slowly relaxing end groups.…”
Section: Monolignol Ratio and Linkages Due To Hsqc Nmrmentioning
confidence: 99%
“…In recent years, apart from its combustion for energy, isolation of lignin originating from industrial kraft pulping processes as well as biorefinery plants producing ethanol as biofuel has seen a steady increase. Parallel to the surge in the availability of lignin, nano‐ and microscaled lignin‐based materials and state‐of‐the‐art analytical techniques that provide a more detailed understanding of the structural differences of the various lignins were developed …”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Lancefield et al reported a study on lignin 3D structure analysis using attenuated total reflection (ATR)-FTIR analysis combined with PCA and PLS modeling. In addition, the obtained quantitative results were comparable to gel-permeation chromatography (GPC) and 2D heteronuclear single quantum coherence (HSQC) nuclear magnetic resonance (NMR) methods [131].…”
Section: Spectroscopic Data Processing Using Chemometric Methods For mentioning
confidence: 67%
“…Within the last five years, a tremendous number of LCF analysis studies have been reported, some of which include chemometric data processing (Table 3) [131,134]. For example, in 2014 Da Costa et al reported an LCF cell-wall analysis study, including 25 Miscanthus genotypes of different developmental stages separated into stem and leaf portions.…”
Section: Chemometrics Used For Ligocellulose Feedstock Specificationmentioning
confidence: 99%